Measuring child functioning: Assessing correlation and agreement between caregiver and child responses at the Iganga-Mayuge health and demographic surveillance site in Uganda. Issue 2 (April 2021) - Zia, Nukhba; Bachani, Abdulgafoor M.; Kajungu, Dan; Galiwango, Edward; Loeb, Mitchell; Diener-West, Marie; Wegener, Stephen; Pariyo, George; Hyder, Adnan A.
Abstract: Introduction: Empirical data is scare on assessment of concordance between caregiver-child responses on child functioning. Objective: To assess correlation and agreement between children (11–17 years old) and their caregivers' responses to the UNICEF/Washington Group Child Functioning Module (CFM) at the Iganga-Mayuge Health and Demographic Surveillance Site (IM-HDSS) in Uganda. Methods: CFM with 24-questions corresponding to 13 domains of functioning was administered to children between 11 and 17 years of age and their caregivers. Descriptive analyses of the child/caregiver responses were conducted. Correlation and agreement between caregiver and child responses were assessed. Results: Of the 217 caregiver/child pairs eligible for this study, 181 pairs agreed to participate (83.4%). The mean age of children was 13.9 ± 1.9 years, and 56.4% were males. Cronbach's alpha was 0.892 and 0.886 for the caregiver and child versions of CFM respectively, showing good internal consistency in both. There was a significant overall agreement between mean score of caregiver (5.36 ± 5.63 out of 39) and child (5.45 ± 5.34) pairs. Spearman's rank correlation between the pairs was 0.806 (strong positive correlation). Bland-Altman plots for CFM scores showed greater agreement between caregiver and child at lower scores. Percentage agreement between the pairs for overall disability was greater for mild (83.53%) and moderate (79.37%) categories as compared to the severe (66.67%) category. There was substantial agreement (kappa 0.623) for overall disability between the pairs. Conclusion: This study indicates that there is significant correlation and agreement between self-reported caregiver-child pair responses, opening the way for considering children as CFM respondents, when possible.